Tripping Through Headlines: Psychedelics in Aotearoa New Zealand’s News Media - Ko, Matthew (Auckland University of Technology, 2024)
Background: The past two decades have seen a revivification of research into psychedelic substances, resulting in a solid base of clinical data proving efficacy for the treatment of mental health diagnoses. The use of certain psychedelics for mental health therapy was legalized in Australia in 2023, sparking discussion around the prospects of Aotearoa New Zealand following suit. Key stakeholders in the Australian psychedelic market have identified the stigma associated with psychedelics as a major barrier to progress and stress the need for effective communication strategies for re-education. To contribute to this initiative, this thesis analyzed domestic news media coverage to provide a foundational understanding of the prevailing discourse around psychedelics to help guide and inform future communication strategies and re-education efforts Methods: This research employs a thematic content analysis method to examine written news media content from Aotearoa New Zealand, sourced from the years 2000-2023. An inductive coding method was used to determine emergent themes and voices present in the articles. This thesis measured both how many articles referenced each theme and sub-theme, and the total number of times each theme and sub-theme was referenced overall. This provided two data metrics to demonstrate both the breadth and depth of themes in the reporting. Filtering this data to only include articles which contained a specific voice for third-party comment demonstrated how different types of outside commentary affected the thematic content of the coverage. Results: Seventy-five (75) articles met the inclusion criteria. Analysis yielded six themes, 23 sub-themes and five types of voices. The “Potential Benefits” theme, categorizing reporting on the various proposed benefits of psychedelic use, was referenced in the most articles (n=67 of 75) indicating it was the most widely covered topic. The “Clinical Studies” theme, categorizing coverage of the processes and results of clinical trials with psychedelics, received the most total references (n=463), indicating it was the topic which received the most in-depth reporting. Conclusion: This research concluded that psychedelics have predominantly been portrayed as a pharmaceutical aid to psychotherapy in the Aotearoa New Zealand news media. This has primarily been achieved through commentary from ‘researcher voices’. The data in this thesis demonstrated that the inclusion of other types of voices greatly affected the thematic content of the reporting. As such, the dominance of ‘researcher voices’ caused other topics and important narratives regarding psychedelics to be muted and overlooked in the coverage. For the prospective psychedelic industry to overcome stigma through re-education, this research suggests that it is imperative that their communication strategies include a variety of voices to adequately address important information and provide holistic teaching from diverse perspectives.